2007
DOI: 10.1080/02652040701585179
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyurethane nanocapsules by miniemulsion polyaddition

Abstract: The encapsulation of organic liquids in polyurethane nanocapsules by interfacial miniemulsion polycondensation of isophorone diisocyanate and propanetriol has been performed. The influence of type and amount of encapsulated organic liquid has been studied and it was found that the encapsulation efficiency is dependent on the water solubility of the organic liquids, their interfacial tension against water and their compatibility with polyurethane. It was also shown how different types of surfactants and variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Study on polyurethane microcapsules by Frere et al (1998) shows that diameter of microcapsules increases as temperature is increased, but mechanical resistance decreases with increase of diameter. It was observed that different types of surfactants and variation in pH and ionic strength of the continuous phase affected the diameter of the mini-emulsion droplets and the resulting microcapsules (Johnsen and Schmid, 2007).…”
Section: -Severalmentioning
confidence: 99%
“…Study on polyurethane microcapsules by Frere et al (1998) shows that diameter of microcapsules increases as temperature is increased, but mechanical resistance decreases with increase of diameter. It was observed that different types of surfactants and variation in pH and ionic strength of the continuous phase affected the diameter of the mini-emulsion droplets and the resulting microcapsules (Johnsen and Schmid, 2007).…”
Section: -Severalmentioning
confidence: 99%
“…• The encapsulation of organic liquids in PUR nanocapsules prepared by interfacial miniemulsion polycondensation of isophorone diisocyanate and propanetriol has also been reported [52] . Encapsulation effi ciency was found to be dependent on the water solubility, interfacial tension against water, and compatibility with PUR of the liquids.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…Nanocapsules have a polymeric shell and an inner liquid core. In this case, the active substances are usually dissolved in the inner core, but may also be adsorbed to their surface (Limayem et al 2004;Johnsen and Schmid 2007;Letchford and Burt 2007;Moinard-Che´cot et al 2008). …”
Section: Introductionmentioning
confidence: 98%